Microscopic Examination of Fecal Leukocytes as a Simple Method to Detect Infective Colitis in Children - Nuraini I Susanti; Reynaldo Reynaldo; Aria Kekalih; Anis Karuniawati; Badriul Hegar (The Indonesian Society for Digestive Endoscopy, 2017)
Background: Various pathogenic bacteria are reported as the cause of infectious colitis in children. Infectious colitis does not have a specific sign, therefore an accurate examination is required. The implementation of fecal cultures accompanied with drug resistance tests often have constraints, beside the relatively expensive costs, longer times are needed, and not all health care facilities have required instruments. On the other hand, this condition requires an immediate antibiotic therapy, so that the infection should not be continued. In daily practice, it is not uncommon to find diarrhea with the amount of fecal leukocyte 10/hpf with pathogenic bacteria on the examination of the fecal culture.Method: Cross-sectional study was conducted to observe the pattern of bacterial distribution in children’s fecal who have acute diarrhea and the correlation between the existence of pathogenic bacteria and the number of leukocytes in the fecal, as well as antibiotic resistance patterns. The population of this study is children with age of 6 months old - 18 years old who were suffering from acute diarrhea with the amount of fecal leucocyte ≥ 5/hpf, who recruited from polyclinic or patient admitted at Cipto Mangunkusumo Hospital and Fatmawati General Hospital, Jakarta.Results: Based on examinations of fecal cultures and PCR, Salmonella sp and C. dificille were found subsequently in 2 children (33.3%), Enterophatogenic E. Coli(EPEC) and Shigella were found subsequently in 1 child (16.7%). Based on the ROC curve, it was found that there was no intersection of maximum and minimal leukocyte value with the midline, whereas the best sensitivity and specificity value was found at the cut-off point of 8.5, hence the cut-off point of leukocytes was determined at 8 and 8. The sensitivity value was 83.3% and the specificity value was 45.1%.Conclusion: The antibiotic sensitivity test showed that one child infected by EPEC was sensitive to ciprofloxacin. Two children infected by Salmonella, were still sensitive to chloramphenicol, cotrimoxazole, cefixime, and ceftriaxone. Two children infected by C. Difficile were sensitive to ceftriaxone, and 1 child infected by Shigella was sensitive to cefixime, ceftriaxone and ciprofloksazine.